Stress Analysis with Different Geometry of Water Tank: Exploring the Effects of Different Geometries on Stress Analysis of Water Tanks (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Recent trends in construction become indispensable within the coming years to emphasize on sustainable development. The paper discusses the importance and scope of recent trends in construction techniques. The paper emphasizes on exploitation differing kinds of materials in modern trends and for effectiveness in infrastructure building for fast economic process and development of a nation exploitation recent advancements within the field of construction technology. Nowadays, the prefabrication and aluminium Formwork technique in trade construction industry is developed countries has improved the standard of the construction industry. Aluminium Formwork System is a construction system for forming cast in situ concrete structure of a building. Classified information‘s given for Aluminium Formwork technique and Conventional techniques. Two case studies are taken for the analysis of the construction techniques. The concept of formed (also called ―prefabricated‖) construction includes those buildings wherever the bulk of structural parts are standardized and created in plants during a location far from the building, so transported to the location for assembly